Representação dos processos hidrológicos em bacia hidrográfica do semiárido paraibano com modelagem hidrológica distribuída - Felix, Vagner de Souza (2015)
Distributed hydrological modeling can help spatio-temporal representation of hydrological processes in a catchment area. The distributed hydrologic model for large basins MGB - IPH has been applied in various Brazilian and South American river basins, but has been little used in intermittent rivers basin. The semi-arid region is characterized by having a large climate variability, dry and shallow soils, and with outcrops of crystalline rocks, factors that may have a huge influence for distributed hydrological modeling. In this sense, it is necessary to develop and improve hydrological models to simulate such complex behavior. In addition, understanding the hydrological processes of the semiarid region may help in the planning and management of water resources. Thus, the main objective of this research is to analyze the performance of the distributed hydrological model MGB-IPH in representing the spatio-temporal patterns of hydrological processes in the Piancó river catchment (PB). In this study, hydrological modeling covers part of the Piancó river catchment, one located upstream of the Piancó gauging station, with an area of 4603.39 square kilometers. The MGB-IPH model was run with daily time step time thereafter flows were generated on a monthly time step. Fourteen rainfall stations and the runoff station of Piancó (ANA Code 37340000) were used. From the analysis of vegetation cover, land use and soil type, 7 hydrological response units (HRUs) were defined, they are: Argisoils/Caatinga, litosoils/caatinga, cambisoils/caatinga, argisoils/agriculture, luvisoils/agriculture, lítosoils/agriculture. A 0.05 x 0.05o square-grid spatial discretization was adopted, i.e. cells of approximately 5 x 5 km. The MGB-IPH model was applied for a period of 42 years (1970-2011), considering each period of 21 years for calibration and validation. The model was calibrated in two versions, one manually and another automatically, by using an optimizing algorithm. In addition to the objective functions commonly used in the model calibration and validation (Nash-Sutcliffe coefficient for discharges, this same coefficient for logarithms of discharges, and volume error), two other metrics were used for results evaluation, which are the normalized benchmark efficiency (BE) and the volumetric efficiency ratio (VE), but these equations were not used to calibrate the model. The results showed that MGB-IPH model satisfactorily represented observed flow regime. The coefficient of Nash-Sutcliffe (NS) for manual calibration daily level was 0.70 and for automatic calibration was 0.72. In the validation period, daily NS was 0.65, while at monthly basis NS was about 0.84. Thus, it can be concluded that the MGB-IPH hydrologic model is applicable and has potential do simulate the hydrological processes in a daily basis in intermittent river catchments.